Measuring health related quality of life of care home residents, comparison of self-report with staff proxy responses for EQ-5D-5L and HowRu: protocol for assessing proxy reliability in care home outcome testing - Usman, Adeela; Lewis, Sarah; Hinsliff-Smith, Kathryn; Long, Annabelle; Housley, Gemma; Jordan, Jake; Gage, Heather; Dening, Tom; Gladman, John R.F.; Gordon, Adam L. (BMJ Publishing Group Ltd, 2018)
Introduction Research into interventions to improve health and wellbeing for older people living in care homes is increasingly common. Health-Related Quality of Life (HRQoL) is frequently used as an outcome measure but collecting both self-reported and proxy HRQoL measures is challenging in this setting. This study will investigate the reliability of UK care home staff as proxy respondents for the EQ-5D-5L and HowRu measures.